2022
DOI: 10.1073/pnas.2202631119
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1 SUMOylation coordinates endothelial angiogenic signaling in angiogenesis

Abstract: Angiogenesis contributes fundamentally to embryonic development, tissue homeostasis, and wound healing. Basic fibroblast growth factor (FGF2) is recognized as the first proangiogenic molecule discovered, and it facilitates angiogenesis by activating FGF receptor 1 (FGFR1) signaling in endothelial cells. However, the precise roles of FGFR and the FGF/FGFR signaling axis in angiogenesis remain unclear, especially because of the contradictory phenotypes of in vivo FGF and FGFR gene deficiency models. Our previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…37 Our previously obtained data showed the role of SENP1mediated deSUMOylation in ischemia and vascular defects, 38 and our studies also revealed the pivotal role of SUMOylation in endothelial activation in graft arteriosclerosis and endothelial growth in angiogenesis. [39][40][41] In the present study, we uncovered an intrinsic SUMOylationmediated regulation of mitochondrial homeostasis in pulmonary ECs to preserve pulmonary endothelial function in response to hypoxic stress during PH.…”
Section: Nonstandard Abbreviations and Acronymsmentioning
confidence: 79%
“…37 Our previously obtained data showed the role of SENP1mediated deSUMOylation in ischemia and vascular defects, 38 and our studies also revealed the pivotal role of SUMOylation in endothelial activation in graft arteriosclerosis and endothelial growth in angiogenesis. [39][40][41] In the present study, we uncovered an intrinsic SUMOylationmediated regulation of mitochondrial homeostasis in pulmonary ECs to preserve pulmonary endothelial function in response to hypoxic stress during PH.…”
Section: Nonstandard Abbreviations and Acronymsmentioning
confidence: 79%
“…Six isoforms of SENPs have been identified in humans (SENP1, SENP2, SENP3, SENP5, SENP6, and SENP7) [ 16 ]. While previous studies have mainly focused on the pivotal role of SENPs in the development of cancer [ 17 , 18 , 19 , 20 , 21 , 22 ], in recent years, the role of SENPs and SUMOylation in vascular diseases has attracted considerable attention [ 14 , 23 , 24 , 25 , 26 , 27 ]. SENP1 modulates the SUMOylation of GATA2 and leads to endothelial dysfunction in graft atherosclerosis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… 997 The dynamic SUMOylation of endothelial FGFR1 regulates the balance of the angiogenesis core pathways VEGF/VEGFR and FGF/FGFR and enables the body to complete angiogenesis in different microenvironments. 1003 SUMOylation also plays an important role in the generation of germ cells. SUMO1 and SUMO2/3 function at different stages of male meiosis and precisely regulate the formation of sex chromosomes.…”
Section: Sumoylationmentioning
confidence: 99%
“…Endothelial SENP1 deletion in newly generated mice significantly delayed retinal vascularization by maintaining prolonged NOTCH1 signaling 997 . The dynamic SUMOylation of endothelial FGFR1 regulates the balance of the angiogenesis core pathways VEGF/VEGFR and FGF/FGFR and enables the body to complete angiogenesis in different microenvironments 1003 . SUMOylation also plays an important role in the generation of germ cells.…”
Section: Sumoylationmentioning
confidence: 99%